1993
DOI: 10.1021/jm00067a017
|View full text |Cite
|
Sign up to set email alerts
|

Studies on quinazolines. 5. 2,3-Dihydroimidazo[1,2-c]quinazoline derivatives: a novel class of potent and selective .alpha.1-adrenoceptor antagonists and antihypertensive agents

Abstract: A series of 2-[(substituted phenylpiperazin-1-yl)methyl]- and 2-[(substituted phenylpiperidin-1-yl)methyl]-2,3-dihydroimidazo[1,2- c]quinazolin-5(6H)-ones or -5(6H)-thiones, and 3-[(substituted phenylpiperazin-1-yl)methyl]-2,3-dihydroimidazo[1,2-c]quinaz oline derivatives were synthesized, as conformationally restricted analogues of SGB-1534 and ketanserin, for evaluation as alpha-antagonists and antihypertensive agents. Most compounds containing a (substituted phenylipiperazinyl)methyl side chain displayed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 9 publications
3
33
0
1
Order By: Relevance
“…However, this nonpeptide ligand for FPRL1 may serve as the nucleus for further structural modifications leading to the discovery of more potent and efficacious agonists. Based on published data, it is possible to develop quinazolinone derivatives with higher binding affinities for cell surface receptors including GPCRs (Oshita et al, 1986;Chern et al, 1993;Padia et al, 1998). The selective activation property of Quin-C1 will be of particular interest for future development of small molecular weight, nonpeptide compounds devoid of cell-stimulating functions associated with tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, this nonpeptide ligand for FPRL1 may serve as the nucleus for further structural modifications leading to the discovery of more potent and efficacious agonists. Based on published data, it is possible to develop quinazolinone derivatives with higher binding affinities for cell surface receptors including GPCRs (Oshita et al, 1986;Chern et al, 1993;Padia et al, 1998). The selective activation property of Quin-C1 will be of particular interest for future development of small molecular weight, nonpeptide compounds devoid of cell-stimulating functions associated with tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,5-tetrahydro imidazo [2,1-b] quinazoline as antihypertensive agent (Loev et al, 1971). 5-2,3 dihydro imidazo [1,2-c] quinazoline derivatives as potent and selective a 1 -adrenoceptor antagonists and antihypertensive agents (Chern et al, 1993). A novel class of 6-thiazolyl quinazolines as selective inhibitors of both ErbB-2 and EGFR tyrosine kinase activity was reported (Gaul et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-binding studies indicated that the affinity constant (K i ) of DL-028 for · 1 -adrenoceptors is around 2 ! 10 -10 mol/l, and its affinity for · 1 -receptors is more than 2,000-fold greater than that for · 2 -receptors [13]. In the present study, we assessed the hemodynamic effects of both DL-028 and prazosin in portal hypertensive rats.…”
Section: Introductionmentioning
confidence: 93%
“…For each dose of either drug, it was confirmed that infusion of vehicle (1% dimethyl sulfoxide) did not alter any of the hemodynamic parameters (tables 1, 2). Drugs DL-028 was synthesized and characterized as described in a previous paper [13]. Prazosin was purchased from Sigma Chemical Co. (St. Louis, Mo., USA).…”
Section: Pressure Measurementmentioning
confidence: 99%
See 1 more Smart Citation